Work-Family Life Courses and Metabolic Markers in the MRC National Survey of Health and Development. - Rebecca E Lacey; Meena Kumari; Amanda Sacker; Mai Stafford; Diana Kuh; Anne McMunn (PLoS ONE)
The aim was to investigate whether the combined work-family life courses of British men and women were associated with differences in metabolic markers-waist circumference, blood pressure, high density lipoprotein cholesterol, triglycerides, and glycated haemoglobin-in mid-life. We used data from the Medical Research Council's National Survey of Health and Development-the 1946 British birth cohort. Multi-channel sequence analysis was used to create a typology of eight work-family life course types combining information on work, partnerships and parenthood between ages 16-51. Linear regression tested associations between work-family types and metabolic outcomes at age 53 on multiply imputed data (20 imputations) of >2,400 participants. Compared with men with strong ties to employment and early transitions to family life, men who made later transitions to parenthood and maintained strong ties to paid work had smaller waist circumferences (-2.16cm, 95% CI: -3.73, -0.59), lower triglycerides (9.78% lower, 95% CI: 0.81, 17.94) and lower blood pressure (systolic: -4.03mmHg, 95% CI: -6.93, -1.13; diastolic: -2.34mmHg, 95% CI: -4.15, -0.53). Married men and women who didn't have children had increased high density lipoprotein cholesterol (7.23% higher, 95% CI: 0.68, 14.21) and lower waist circumferences (-4.67cm, 95% CI: -8.37, -0.97), respectively. For men later transitions to parenthood combined with strong ties to paid work were linked to reduced metabolic risk in mid-life. Fewer differences between work-family types and metabolic markers were seen for women.